PENGARUH DOSIS PUPUK K DAN WAKTU APLIKASI PUPUK N TERHADAP PERTUMBUHAN TANAMAN DAN PRODUKSI KEDELAI (Glycine max L. Merril) - Yazid Suhadi; Aslim Rasyad; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this research is to determine the effect of K fertilizer rates and time of N fertilizer application, and to obtain better combination of K fertilizer and time of N fertilizer application for plant growth and soybean grain yield. A Field trial was conducted using a randomized block design with three replications. The rates of K fertilizer were 25 kgK2Oha-1, 50 kgK2Oha-1, and 75 kgK2Oha-1and time of N fertilizer application including,planting date, 30 days after planting, and at plantingdate followed at 30 days after planting. Parameters observed are plant height, number of internodes, seed dry weight at 15, 22 days after pollination and at harvest, dry matter accumulation rate, effective filling period, seed yield m-2, 100-seed weight and harvest index. Significant effect were observed for seed yield per m2 and seed dry weight at harvest, while plant height, number of internodes, seed dry weight at 15 and 22 days after pollination, dry material accumulation rate, effective filling period, 100-seed weight and harvest indexwere not influenced by K fertilizer and time of N application.Keyword :soybean, K fertilizer rates, application time N